Mineralogy and geochemistry of oil sands froth treatment tailings: Implications for acid generation and metal(loid) release. (March 2019) - Lindsay, Matthew B.J.; Vessey, Colton J.; Robertson, Jared M.
Abstract: Froth treatment tailings (FTT) are one of three principal tailings streams generated during bitumen extraction at oil sands mines in northern Alberta, Canada. Unlike the coarse tailings and fluid fine tailings, FTT are enriched in sulfide-minerals and exhibit the potential for acid generation and metal(loid) leaching. However, the mineralogical and geochemical characteristics of this sulfide-bearing tailings stream remain poorly constrained. We examined samples of fresh FTT ( n = 3) and partially-weathered FTT collected from a sub-aerial beach deposit ( n = 15). X-ray diffraction revealed that weathering-resistant silicates, phyllosilicates, and oxides dominated (85 ± 7.3 wt %) the FTT mineral assemblage, while sulfides (6.2 ± 3.6 wt %) and carbonates (8.9 ± 4.3 wt %) were relatively minor phases. Pyrite [FeS2 ] was the principal sulfide in all samples, while minor amounts of marcasite [FeS2 ] occurred only in beach samples. Sulfide mineral textures were highly variable and included euhedral to subhedral pyrite crystals, discrete and clustered pyrite framboids, and marcasite overgrowths on pyrite framboids. Siderite [FeCO3 ] accounted for 55–90% of all carbonates, while dolomite [CaMg(CO3 )2 ], calcite [CaCO3 ] and ankerite [Ca(Fe, Mg, Mn)(CO3 )2 ] accounted for the remainder. Statistical analysis of bulk geochemical compositions suggested that environmentally-relevant metal(loid)s, including As, Cu, Co, Fe, Mn, Ni, Pb and Zn, were likely associated with sulfides, carbonates and, to a lesser extent, phyllosilicates. Electron probe microanalyses revealed a wide range of As, Cu, Co, Mn, Ni and Zn concentrations in pyrite, with As and Cu concentrations elevated in framboids. Rare earth elements (REEs), Th and U also occurred at elevated concentrations and statistical analyses suggest they are associated with zircon and, potentially, monazite and xenotime. Static acid-base accounting (ABA) tests indicated that all FTT samples are potentially acid generating. Our study describes the mineralogical and geochemical characteristics of oil sands FTT, and indicates that oxidative weathering has the potential to generate acidic drainage containing elevated dissolved concentrations of several metal(loid)s. Highlights: Mineralogy and geochemistry of oil sands froth treatment tailings is described. Pyrite and siderite are the principal sulfide and carbonate minerals, respectively. Marcasite, dolomite, calcite and ankerite also detected. Pyrite contains elevated As, Cu, Co, Mn, and Ni concentrations. Froth treatment tailings exhibit potential for acid generation and metal(loid) release.